Steel Material Degradation Assessment Via Vibro-Acoustic Modulation Technique. Issue 10 (October 2019) - Ramezani, Majid G.; Golchinfar, Behnoush; Donskoy, Dimitri; Hassiotis, Sophia; Venkiteela, Giri
The increasing probability of collapse in defective structures owing to aging is one of the major issues in transportation. Therefore, different methodologies that are capable of monitoring structural components have been used to identify defects and predict failure. Among these methods, the non-linear vibro-acoustic modulation (VAM) technique has been implemented for many years in a variety of industries, such as aerospace. This method utilizes the effect of nonlinear interactions between a high frequency ultrasonic wave (carrier signal) and a much lower frequency structural vibration (modulating signal). This interaction takes place at nonlinear interfaces (cracks, bolted connections, delaminations, etc.) manifesting itself in the spectrum as side-band components around the carrier frequency. In this study, the VAM method was investigated as a non-destructive evaluation (NDE) method for fracture critical members (FCMs) in steel bridges. The results of the experimental studies revealed that using the VAM technique on test specimens during the tension only fatigue tests would provide some useful information on the existence of micro-cracks and on failure prediction. The use of the VAM technique for center-notched rectangular test specimens of structural steel under low-amplitude fatigue loading at a frequency of 10 Hz is capable of predicting the failure at 70–80% of the fatigue lifetime of the specimen. Moreover, in this investigation utilizing fatigue cycling as a modulating signal was successfully substituted for the conventional utilization of resonance structural bending vibrations.